Cerium dioxide material containing oxygen vacancies as well as preparation method and application thereof
Through the high-temperature calcination method of generating oxygen vacancy defects on the surface of ceria, the problem of insufficient response of ceria to the near-infrared region is solved, the light absorption range is widened and the photothermal conversion efficiency is improved, and its application in many fields is expanded.
Patent Information
- Application Number
- CN202510387047.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-31
AI Technical Summary
The existing ceria materials have insufficient light response in the near-infrared region, making it difficult to broaden the light absorption range, limiting their application in the fields of chemical industry, energy, sensing and life and health.
The oxygen vacancy defect is generated on the surface of ceria by high-temperature calcination, which reduces the band gap and trap carriers of the photocatalytic reaction, and expands the light absorption into the visible region and the near-infrared region.
The photocatalytic activity and photothermal conversion efficiency of ceria are improved, the rapid heating characteristics are achieved, and its multifunctional application in elastomers is expanded.
Smart Images

Figure CN119875393A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional nanomaterials, and in particular relates to a cerium dioxide material containing oxygen vacancies, a preparation method and an application thereof. Background Art
[0002] The physical and chemical properties of rare earth oxide CeO2 directly affect the performance of materials. It has been widely used in luminescent materials, polishing agents, ultraviolet absorbers, automobile exhaust purification catalysts, chemical decolorizers for glass, radiation-resistant glass, electronic ceramics, etc. The special structure of CeO2 is easy to convert between trivalent and quadrivalent, and there is a strong ability to store and release oxygen during the interchange process. Nano-cerium dioxide still retains the unique 4f electronic layer structure of rare earth elements, has a wide band and strong absorption capacity, and has a strong absorption capacity for ultraviolet rays. Adding nano-CeO2 to polymer materials can slow down the aging speed and reduce the damage of ultraviolet rays. The electronic layer structure of rare earth elements has a large number of empty orbits and has a strong ability to combine with free radicals. The complexes formed with certain compounds containing O, N, and S atoms have a significant effect in inhibiting the long-term thermal oxidation aging of elastomers. At present, the application of nano-cerium dioxide as a new generation of efficient, environmentally friendly and safe antioxidants in elastomer materials has made certain progress.
[0003] Cerium dioxide is a wide-bandgap semiconductor that absorbs mainly in the ultraviolet region and almost does not absorb in the visible light range, less than 5% of the solar spectrum energy, and cannot generate enough heat under sunlight or laser irradiation. Therefore, it is urgent to solve the problem of its response to near-infrared light and expand the light absorption range, so as to better serve the chemical industry, energy, sensing and life health fields as a new type of photothermal filler.
[0004] The design of defective materials is a feasible solution. The complete and orderly arrangement of the crystal structure is an ideal situation. In practical applications, most materials are defective rather than in an ideal state. Crystal defects are considered to be periodic structural distortions of the crystal produced by molecules or atoms in the crystal. Due to the profound effects of defects on light absorption, charge separation and interface reactions, defect engineering has also attracted widespread attention in photocatalytic materials. Defects are an important parameter in the design of photocatalysts. They usually affect the band structure, state density and surface properties of semiconductors, thereby giving semiconductors enhanced light capture ability, surface interaction or charge transfer efficiency. Among them, vacancies are one of the classic point defects, which are caused by the absence of atoms. Oxygen vacancies are the most widely studied anion vacancies. For oxide materials, in some cases, the escape of lattice oxygen will lead to the loss of oxygen, thereby forming oxygen vacancies. The formation of oxygen vacancy defects can narrow the band gap and trap carriers of the photocatalytic reaction, thereby improving the photocatalytic activity. Secondly, surface oxygen vacancy defects can capture electrons or holes and inhibit the recombination of photogenerated carriers.
[0005] Although the traditional hydrothermal method can introduce oxygen vacancies into the material, its process conditions are relatively strict. In addition to high temperature, it also requires a high-pressure environment and is highly dependent on production equipment. In addition, the reaction is prone to side reactions, and it is difficult to separate and purify the products. In addition, the pretreatment time for the uniform dispersion of cerium oxide and sodium borohydride in the traditional hydrothermal process is too long. At the same time, it is difficult to avoid the problem of cerium oxide settling at the bottom during the transfer to the hydrothermal kettle, and it is impossible to ensure that cerium oxide is reduced under uniform medium conditions. More importantly, although the traditional hydrothermal method may make the oxygen vacancies more evenly distributed, the too low oxygen vacancy density makes it difficult to broaden the visible light absorption capacity, resulting in poor photothermal performance. At present, research on new preparation methods for cerium dioxide materials containing oxygen vacancies has not been widely reported, and its feasibility as a photothermal filler in elastomers needs further exploration. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a cerium dioxide material containing oxygen vacancies, and a preparation method and application thereof. The present invention generates crystal defects on the surface of cerium dioxide while retaining the original overall structure intact through a high-temperature calcination method. Periodic structural distortions, namely oxygen vacancy defects, occur at the edges of cerium dioxide crystals, thereby reducing the bandgap and trap carriers of the photocatalytic reaction, so that the light absorption of cerium dioxide can be effectively extended to the visible region and near-infrared region, and the absorption in the visible light region is improved, thereby improving the photocatalytic activity and having excellent photothermal conversion efficiency and rapid heating characteristics; at the same time, high-temperature calcination volatilizes the crystal water and organic impurities in the material, rearranges the crystal structure, modifies the surface of the material, improves the thermal stability of the material, and realizes the possibility of cerium dioxide as a photothermal material. More importantly, high-temperature calcination can also significantly improve the warming effect and photothermal conversion efficiency of the material.
[0007] Furthermore, the prepared cerium dioxide containing oxygen vacancies is used as a multifunctional filler in elastomers. Taking advantage of its excellent thermal stability, photocatalytic activity, photothermal conversion efficiency and rapid heating characteristics, it can be used as an antioxidant, UV absorber, heat stabilizer, photothermal agent, and reinforcing agent at the same time, expanding the application field of cerium dioxide materials. As a new type of photothermal filler, it can better serve the chemical, energy, sensing and life and health fields.
[0008] In addition, the preparation method of the present invention greatly simplifies the traditional preparation process of cerium dioxide-based photothermal materials and improves the material preparation efficiency; at the same time, the method is suitable for cerium dioxide of various sizes and morphologies.
[0009] The purpose of the present invention can be achieved by the following scheme: In a first aspect, the present invention provides a method for preparing a cerium dioxide material containing oxygen vacancies, comprising the following steps: S1. Under an inert atmosphere, mixing cerium dioxide with a reducing agent and calcining the mixture to obtain a crude cerium dioxide product containing oxygen vacancies; S2. Washing the crude cerium dioxide product to obtain the cerium dioxide material.
[0010] As an embodiment of the present invention, in step S1, the cerium dioxide is a cerium dioxide powder obtained by vacuum dehydration at 60-90° C. The sources of the cerium dioxide powder in the present invention include but are not limited to commercially available, detonation method, microwave method, melting method, solid phase synthesis method, carbon adsorption combustion method, precipitation method, sol-gel method, hydrothermal reaction method, and polyethylene glycol gel method.
[0011] As an embodiment of the present invention, in step S1, the reducing agent includes at least one of charcoal, hydrogen sulfide, potassium iodide, potassium thiosulfate, ascorbic acid, sodium borohydride, sodium sulfide, formaldehyde, and oxalic acid, preferably sodium borohydride, which is stable to moisture and suitable for industrial production.
[0012] As an embodiment of the present invention, in step S1, the mass ratio of the cerium dioxide to the reducing agent is 1:0.2 to 1:1. If the proportion of the reducing agent in the system is too low, the cerium dioxide is difficult to be effectively reduced; if the proportion of the reducing agent in the system is too high, the oxide or decomposition product is difficult to remove, resulting in cumbersome purification steps of the subsequent oxygen vacancy cerium dioxide.
[0013] In some embodiments, the mixing is performed using a porcelain ark, and the calcination is performed in a high temperature tube furnace.
[0014] As an embodiment of the present invention, in step S1, the calcination temperature is 600-750°C and the time is 1h-8h. If the temperature is too low, the reaction is slow and cerium dioxide cannot generate vacancy defects within a limited time; if the temperature is too high, cerium trioxide or cerium alone may be reduced, which is inconsistent with the expected effect. In addition, the reaction time is related to the calcination temperature. Ideally, the longer the reaction time, the higher the oxygen defect concentration. It is more reasonable to preferably set 8h as the maximum reaction time.
[0015] In some embodiments, the inert atmosphere includes at least one of nitrogen and argon.
[0016] As an embodiment of the present invention, in step S2, the washing process comprises: washing with water and ethanol alternately and centrifuging, and repeating 2-4 times. In some embodiments, after washing, vacuum drying is performed to obtain cerium dioxide containing oxygen vacancies, and the temperature of the vacuum drying is 50-80° C. The function of washing is to remove the products produced after the reducing agent is oxidized or decomposed.
[0017] In a second aspect, the present invention provides a cerium dioxide material obtained by the preparation method.
[0018] In a third aspect, the present invention provides a use of the cerium dioxide material in the preparation of a composite elastomer material.
[0019] As an embodiment of the present invention, the composite elastomer material is prepared by the following steps: Step 1: mixing the cerium dioxide material with hyaluronic acid, and performing a hydrothermal reaction to obtain a hyaluronic acid-modified cerium dioxide material; Step 2: Mix the hyaluronic acid-modified cerium dioxide material with the elastomer and shape them to obtain a composite elastomer.
[0020] As an embodiment of the present invention, in step 1, the solvent used for the mixing is deionized water, and the mixture is stirred at room temperature for 2-4 hours. In some embodiments, the hydrothermal reaction is carried out in a forced air oven.
[0021] As an embodiment of the present invention, in step 1, the mass ratio of the cerium dioxide material to the hyaluronic acid is 1:1 to 1:10. The hyaluronic acid modification is mainly to enhance the CeO 2-x If the mass ratio is too large, some oxygen vacancies on the cerium dioxide surface may not be successfully modified; if the mass ratio is too small, the unmodified hyaluronic acid will be washed away by deionized water, resulting in waste.
[0022] As an embodiment of the present invention, in step 1, the temperature of the hydrothermal reaction is 80-120°C and the time is 6-10 h. In some embodiments, after the hydrothermal reaction, the mixture is washed with deionized water and vacuum dried at 50-80°C to obtain a hyaluronic acid-modified cerium dioxide material.
[0023] As an embodiment of the present invention, in step 2, the elastomer includes any one of rubber, polyurethane, styrene-based thermoplastic elastomer, thermoplastic dynamic vulcanized rubber, and thermoplastic polyurethane elastomer (TPU95A). The elastomer is a polymer material that deforms significantly under weak stress and can quickly recover to a state close to the original state and size after stress relaxation. The sources of the elastomers in the present invention include but are not limited to commercially available or homemade, wherein the preparation method of the polyurethane elastomer comprises: adding hexamethylene diisocyanate to polycaprolactone diol after vacuum dehydration at 75-85°C, stirring evenly, adding triethanolamine and N,N,N',N'-tetra(2-hydroxypropyl)ethylenediamine, and continuing to stir to obtain a polyurethane elastomer, wherein the mass ratio of the polycaprolactone diol, hexamethylene diisocyanate, triethanolamine and N,N,N',N'-tetra(2-hydroxypropyl)ethylenediamine is 2.6-3.4:0.4-0.5:0.04-0.05:0.14-0.18.
[0024] As an embodiment of the present invention, in step 2, the mass ratio of the hyaluronic acid-modified cerium dioxide material to the elastomer is 0.005:1 to 0.2:1.
[0025] As an embodiment of the present invention, in step 2, the mixing method includes mechanical shearing or mechanical stirring.
[0026] As an embodiment of the present invention, in step 2, the molding temperature is 80-160°C.
[0027] Compared with the traditional hydrothermal process, the present invention uses a mortar to mix the cerium oxide powder and the reducing agent powder evenly and then transfers them to the porcelain ark. The pre-treatment steps are simple and efficient, and no additional equipment such as a hydrothermal kettle is required, and the overall process is greatly simplified. In addition, the high-temperature calcination method used in the present invention can achieve thermal stabilization of the material. The crystal water and organic impurities in the material will volatilize at high temperatures, and the crystal structure in the material will be rearranged and combined to modify the surface of the material and improve the thermal stability of the material. More importantly, the high-temperature calcination method used in the present invention can also significantly improve the material heating effect and photothermal conversion efficiency.
[0028] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention generates crystal defects on the surface by a one-step method of high-temperature calcination in an inert gas, and periodic structural distortions occur at the edge of the cerium dioxide crystal, namely oxygen vacancy defects, which reduce the bandgap and trap carriers of the photocatalytic reaction, and enhance the absorption in the visible light region, thereby improving the photocatalytic activity; at the same time, the photothermal conversion efficiency and rapid heating characteristics of the material are also greatly improved, realizing the possibility of cerium dioxide as a photothermal material. Compared with the traditional hydrothermal process, the present invention creatively adopts a high-temperature calcination process, which greatly simplifies the preparation process of cerium dioxide-based photothermal materials and improves the material preparation efficiency; on the other hand, it volatilizes the crystal water and organic impurities in the material, rearranges the crystal structure, modifies the surface of the material, and improves the thermal stability of the material; more importantly, it can also significantly improve the heating effect and photothermal conversion efficiency of the material.
[0029] 2. The present invention uses the prepared cerium dioxide containing oxygen vacancies as a multifunctional filler in an elastomer. It can be used as an antioxidant, ultraviolet absorber, heat stabilizer, photothermal agent, and reinforcing agent due to its excellent thermal stability, photocatalytic activity, photothermal conversion efficiency, cyclically stable photothermal effect, and rapid heating characteristics, thereby expanding the application field of cerium dioxide materials.
[0030] 3. The present invention can synthesize cerium dioxide containing oxygen vacancy defects with different photothermal properties by changing the sintering temperature and sintering time. Different types of cerium dioxide containing oxygen vacancies are analyzed by transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and infrared imager to summarize the factors affecting the material lattice parameters, surface morphology, defect morphology, and photothermal properties, optimize the performance, and obtain a new cerium dioxide photothermal material with visible light absorption and good photothermal properties. Further, by changing the doping ratio of cerium dioxide containing oxygen vacancies in the elastomer, the composite elastomer can have different comprehensive properties, which is of great significance to the improvement of anti-aging, thermal stability, and photothermal conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 These are digital photos of cerium dioxide powders of Comparative Example 1 and Example 1; Figure 2 X-ray diffraction images of Comparative Example 1 and Example 1; Figure 3 The scanning electron microscope images of Comparative Example 1 and Example 1; Figure 4 TEM images of Comparative Example 1 and Example 1; Figure 5 The full X-ray photoelectron spectra of Comparative Example 1 and Example 1; Figure 6 X-ray photoelectron spectroscopy O 1s spectra of Comparative Example 1 and Example 1; Figure 7 X-ray photoelectron spectroscopy Ce 3d spectra of Comparative Example 1 and Example 1; Figure 8 The thermogravimetric test results of Comparative Example 1 and Example 1 are shown in FIG. Fig. 9 Comparative Example 1 was irradiated with 808 nm laser (1 W / cm 2 )’s heating and cooling curves; Fig.10 Example 1 under 808 nm laser irradiation (1 W / cm 2 )’s heating and cooling curves; Fig.11 The temperature rise curve of Example 1 under 808 nm laser irradiation with different power densities; Fig.12 These are digital photos of the cerium dioxide-doped composite polyurethanes of Comparative Example 1 and Example 1. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0033] Example 1 The present invention provides a sodium borohydride-reduced cerium dioxide material containing oxygen vacancies and a preparation method of a composite polyurethane material thereof, comprising the following steps: Step 1: Prepare a crude cerium dioxide product containing oxygen vacancies, the preparation steps are: 1 g of cerium dioxide powder (commercially available spherical cerium dioxide) was vacuum dehydrated at 80 °C, ground and mixed with 0.8 g of sodium borohydride, and then added to the porcelain ark and calcined at 600 °C in nitrogen atmosphere for 3 h; Step 2: Prepare cerium dioxide containing oxygen vacancies, the preparation steps are: The crude product was cooled, washed alternately with water and ethanol, centrifuged three times, and then dried in vacuum at 80°C to obtain cerium dioxide containing oxygen vacancies.
[0034] Step 3: Prepare hyaluronic acid-modified cerium dioxide material containing oxygen vacancies, the preparation steps are: 0.1 g of cerium dioxide containing oxygen vacancies prepared in step 2 was mixed with 1 g of hyaluronic acid in deionized water and stirred at room temperature for 2 h. The mixture was placed in a hydrothermal reactor and reacted in a forced air oven at 80 °C for 6 h. The crude product was washed with deionized water and vacuum dried at 80 °C to obtain hyaluronic acid-modified cerium dioxide containing oxygen vacancies.
[0035] Step 4: preparing a composite polyurethane material doped with cerium dioxide containing oxygen vacancies, the preparation steps are as follows: 3 g of polycaprolactone diol (M n =3000) was vacuum dehydrated at 80 °C, 0.45 g of hexamethylene diisocyanate was added, 0.045 g of triethanolamine and 0.16 g of N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine were added after magnetic stirring, and the polyurethane elastomer was obtained by magnetic stirring. 0.06 g of the hyaluronic acid-modified cerium dioxide material containing oxygen vacancies prepared in step 3 was mixed with the polyurethane elastomer by mechanical stirring, poured into a polytetrafluoroethylene mold and cured at 80 °C to obtain a composite polyurethane material doped with cerium dioxide containing oxygen vacancies.
[0036] Example 2 The preparation method of this embodiment is basically the same as that of embodiment 1, except that the calcination temperature in step 1 is adjusted to 750°C.
[0037] Example 3 The preparation method of this embodiment is basically the same as that of embodiment 1, except that the calcination time in step 1 is adjusted to 1 h.
[0038] Example 4 The preparation method of this embodiment is basically the same as that of embodiment 1, except that the calcination time in step 1 is adjusted to 8 hours.
[0039] Comparative Example 1 The method for preparing the cerium dioxide composite polyurethane material of the present invention comprises the following steps: Step 1: Prepare a cerium dioxide-doped composite polyurethane material, the preparation steps are: 3 g of polycaprolactone diol (M n =3000) was vacuum dehydrated at 80 °C, 0.45 g of hexamethylene diisocyanate was added, 0.045 g of triethanolamine and 0.16 g of N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine were added after magnetic stirring, and the polyurethane prepolymer was obtained by magnetic stirring. 0.06 g of commercial spherical cerium dioxide material was mixed with the polyurethane prepolymer by mechanical stirring, poured into a polytetrafluoroethylene mold and cured at 80 °C to obtain a composite polyurethane material doped with cerium dioxide. The only difference from Example 1 is that the commercial spherical cerium dioxide has no oxygen vacancy defects.
[0040] Comparative Example 2 The preparation method of this comparative example is basically the same as that of Example 1, except that the calcination temperature in step 1 is adjusted to 550°C.
[0041] Comparative Example 3 The preparation method of this comparative example is basically the same as that of Example 1, except that the calcination temperature in step 1 is adjusted to 800°C.
[0042] Comparative Example 4 The preparation method of this embodiment is basically the same as that of embodiment 1, except that the calcination time in step 1 is adjusted to 0.5 h.
[0043] Comparative Example 5 The preparation method of this embodiment is basically the same as that of embodiment 1, except that the calcination time in step 1 is adjusted to 10 h.
[0044] Comparative Example 6 This comparative example provides a method for preparing cerium dioxide material based on a traditional hydrothermal method, comprising the following steps: Step 1: Dehydrate 1 g of cerium dioxide powder (commercially available spherical cerium dioxide) under vacuum at 80 °C, and evenly disperse it with 0.8 g of sodium borohydride in deionized water; transfer it to a hydrothermal reactor for hydrothermal reduction reaction, increase the temperature from room temperature 25 °C to 120 °C at a heating rate of 4 °C / min and maintain the temperature for 5 hours for reaction, then cool it to room temperature 25 °C with the furnace, and finally obtain a cerium dioxide aqueous solution; wash the cerium dioxide aqueous solution with distilled water, filter it, and dry it to obtain a cerium dioxide material.
[0045] Pictures of cerium dioxide powder before and after high temperature reduction Figure 1 As shown in the figure, the commercial spherical nano-cerium dioxide in Comparative Example 1 is a light yellow powder, and the cerium dioxide containing oxygen vacancies in Example 1 is a brown-black powder, which indicates that the generation of oxygen vacancies after high-temperature reduction changes the optical absorption characteristics and exhibits strong absorption in the visible light-near infrared light range. The physical phase test analysis of Comparative Example 1 and Example 1 was carried out by X-ray diffraction. The results are shown in the figure below. Figure 2 As shown, for cerium dioxide nanomaterials, the diffraction peaks at 59.1°, 56.3°, 47.5°, 33.0°, and 28.5° correspond to the (222), (311), (220), (200), and (111) crystal planes of cubic fluorite CeO2 (PDF#34-0394), respectively, while cerium dioxide with oxygen vacancies can still be observed to have diffraction peaks that are roughly consistent with cubic fluorite CeO2, which indicates that cerium dioxide still maintains a good cubic fluorite structure after high-temperature reduction.
[0046] The morphology of cerium dioxide before and after high-temperature reduction was characterized by scanning electron microscopy and transmission electron microscopy. Figure 3-4 As shown, it can be seen that the cerium dioxide nanoparticles did not undergo obvious changes in morphology and size before and after sodium borohydride reduction. In the high-resolution transmission electron microscopy image, it can be found that after high-temperature reduction, an obvious amorphous layer is generated on the surface of cerium dioxide, which indicates that the surface lattice structure is missing and presents a disordered lattice state. This is mainly because a large number of oxygen vacancies are formed on the surface of the material during the high-temperature reduction process.
[0047] In order to further clarify the phase composition of the material and the generation of oxygen vacancies, X-ray photoelectron spectroscopy was used to characterize the chemical composition and element valence state of the material surface. Figure 5 As shown, by comparing the full spectrum scanning results of Comparative Example 1 and Example 1, it is found that the characteristic peak positions and quantities of the two samples have not changed significantly, which indicates that no other heteroatoms are introduced during the doping process. This result is consistent with the transmission electron microscopy results, indicating that the cerium dioxide after high-temperature reduction is only composed of Ce and O. Figure 6-7, it can be observed that the O 1s spectrum of ceria in Comparative Example 1 can be divided into two peaks located at 529.4 and 531.3 eV ( Figure 6 ), they belong to O2 and O-Ce respectively 4+ In the fine spectrum of CeO2 containing oxygen vacancies in Example 1, the lattice oxygen content decreased and the non-lattice oxygen increased significantly, indicating that a large number of oxygen vacancies were generated. In the Ce 3d fine spectrum, it can be observed that the content of non-lattice oxygen increased after preparation. 3+ The proportion of Figure 7 ), the strong peaks with binding energies of 904.0, 900.3, 885.2 and 881.7 eV are attributed to CeO 2-x Center 3+ The above experimental data show that Example 1 prepared a cerium dioxide nanomaterial with oxygen vacancies.
[0048] The above XPS results indirectly prove that the cerium dioxide in Example 1 has a higher thermal stability, because the oxygen vacancies are filled with oxygen, resulting in very little weight loss of the sample at high temperature. Figure 6 In the fine spectrum of ceria before and after the generation of oxygen vacancy defects, the lattice oxygen decreased and the non-lattice oxygen increased significantly. Therefore, the material with more defects significantly enhances the ability to extract surface lattice oxygen species, has more oxygen vacancies to react with oxygen, reduces the degree of its quality degradation, and improves thermal stability. In addition, Figure 8 The thermogravimetric results show that after high-temperature calcination, the first weight loss occurs below 140°C, which is attributed to the loss of adsorbed H2O. At higher temperatures, the thermal stability of cerium dioxide after high-temperature calcination is significantly better than that of uncalcined comparative example 1, proving that the material of the present invention has a certain thermal stability.
[0049] A near-infrared 808 nm laser was selected as the excitation light source, and an infrared thermal imager was used to record the temperature to explore the photothermal heating performance of cerium dioxide containing oxygen vacancies. Figure 9-10 As shown in the figure, the heating curves of Comparative Example 1 and Example 1 before and after high temperature reduction are significantly different. Under the same irradiation power density (1 W / cm 2 ), the cerium dioxide containing oxygen vacancies in Example 1 has excellent photothermal heating performance (i.e., good photothermal conversion efficiency). After 5 minutes of laser irradiation, the temperature difference of the heating is as high as 143.7 °C, while the temperature difference of the commercial cerium dioxide in Comparative Example 1 under the same irradiation conditions is only 31.3 °C. At the same time, the relationship between photothermal heating and irradiation power is also explored. Fig.11 The results show that the minimum power density is 0.5 W / cm 2 The temperature rises to 80.3℃ after 5 minutes of irradiation at 0.75 W / cm 2The temperature rises to 113.7°C after 5 minutes of irradiation, and the maximum power density is 1 W / cm 2 The temperature rises by 143.7°C after 5 minutes of irradiation, which proves that the photothermal effect in Example 1 has obvious power density dependence. The higher the power density, the more obvious the temperature rise. Fig.12 This is a digital photo of polyurethane doped with 2 wt% cerium dioxide. It can be seen that the sample surface is regular and the size is uniform. Cerium dioxide is successfully introduced into the polyurethane system. The sample of Example 1 is darker in color than the sample of Comparative Example 1. Figure 1 The colors of cerium dioxide powder before and after high-temperature reduction correspond.
[0050] Table 1 summarizes the photothermal performance test data of various comparative examples and embodiments. 2 After irradiation for 5 min, the heating temperature and photothermal conversion efficiency in the comparative example are significantly lower than those in the embodiment. On the one hand, if the temperature is too low, the reaction is slow and vacancy defects cannot be generated within a limited time; if the temperature is too high, cerium trioxide or cerium alone may be reduced, which is inconsistent with the expected effect. On the other hand, too short a reaction time results in a small number of oxygen vacancy defects, and too long a reaction time results in energy waste, and there is no further improvement in the photothermal performance. From the results of comparative example 6, it can be seen that the heating effect and photothermal conversion efficiency of the materials prepared by the hydrothermal method are much lower than those of the high-temperature calcination method. Although the hydrothermal process conditions are milder and may make the oxygen vacancy distribution more uniform, the too low oxygen vacancy density makes it difficult to broaden the visible light absorption capacity, resulting in poor photothermal performance. Therefore, the calcination temperature in the present invention is 600-750°C and the time is 1 h-8 h, which is more reasonable.
[0051] Table 1
[0052] In summary, the cerium dioxide containing oxygen vacancies described in the present invention generates a large number of lattice disordered oxygen vacancies on the surface of the material by rationally designing the type of reducing agent, reduction temperature, and reaction time. The light absorption of cerium dioxide is effectively extended to the visible region and near-infrared region. Finally, the material can achieve rapid heating characteristics and can be added to the elastomer matrix as a new type of photothermal filler to realize new functional designs in the fields of chemical industry, energy, sensing, life and health.
[0053] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a cerium dioxide material containing oxygen vacancies, characterized in that: The following steps are involved: S1. Under an inert atmosphere, mixing cerium dioxide with a reducing agent and calcining the mixture to obtain a crude cerium dioxide product containing oxygen vacancies; S2. Washing the crude cerium dioxide product to obtain the cerium dioxide material.
2. The preparation method according to claim 1, characterized in that: In step S1, the cerium dioxide is a cerium dioxide powder obtained by vacuum dehydration at 60-90° C.; the reducing agent includes at least one of carbon, hydrogen sulfide, potassium iodide, potassium thiosulfate, ascorbic acid, sodium borohydride, sodium sulfide, formaldehyde, and oxalic acid.
3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of cerium dioxide to reducing agent is 1:0.2 to 1:
1.
4. The preparation method according to claim 1, characterized in that: In step S1, the calcination temperature is 600-750°C and the calcination time is 1-8 h.
5. The preparation method according to claim 1, characterized in that: In step S2, the washing process includes: washing with water and ethanol alternately and centrifuging, and repeating 2-4 times.
6. A cerium dioxide material obtained by the preparation method according to any one of claims 1 to 5.
7. Use of the cerium dioxide material as claimed in claim 6 in the preparation of a composite elastomer material.
8. The use according to claim 7, characterized in that: The composite elastomer material is prepared by the following steps: Step 1: mixing the cerium dioxide material with hyaluronic acid, and performing a hydrothermal reaction to obtain a hyaluronic acid-modified cerium dioxide material; Step 2: Mix the hyaluronic acid-modified cerium dioxide material with the elastomer and shape them to obtain a composite elastomer.
9. The use according to claim 8, characterized in that: In step 1, the mass ratio of the cerium dioxide material to the hyaluronic acid is 1:1 to 1:10; the temperature of the hydrothermal reaction is 80-120° C., and the time is 6-10 h.
10. The use according to claim 8, characterized in that: In step 2, at least one of the following technical features is also included: The elastomer includes any one of rubber, polyurethane, styrene-based thermoplastic elastomer, thermoplastic dynamic vulcanized rubber, and thermoplastic polyurethane elastomer; The mass ratio of the hyaluronic acid-modified cerium dioxide material to the elastomer is 0.005:1 to 0.2:1; The mixing method includes mechanical shearing or mechanical stirring; The molding temperature is 80-160°C.
Citation Information
Patent Citations
In-situ control method for form and crystal face of nano cerium oxide
CN106904649A
Flame-retardant low-toxicity thermoplastic polyurethane elastomer / cerium oxide nanosheet nano composite material and preparation method thereof
CN107446341A
Nylon elastomer nano composite material and preparation method thereof
CN110229504A
Cerium dioxide nanoparticle AS well AS preparation method and application thereof
CN112494513A
Additive and method for enhancing the heat age properties of elastomers
US6239202B1